Design Methodologies for Steel Structures in Seismic Regions - Rajora, Rohit Kumar; Lamba, Rishabh; Chaudhary, Vishal; Rohit; Dhyani, Ashish (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2014)
This paper is an insight into the recent developments in the design methodologies in seismic design of steel structures. Recent damage throughout the world due to earthquakes have led to the conclusion that the inherent seismic resistance of steelStructures should not be taken for granted. Due to increasing number calamities occurring due to earthquakes per year, new advancements has to be made in the design procedures and material control measures as well as welding practice. We will look into the solutions such as displacementbased design and Assessment procedures alongside the generalization of limit state concepts into a performancebased Design framework. In this paper, recent findings on the material, section, member and sub assemblageLevels are reviewed and possible code applications are highlighted. However our main concern will be moderate seismic zones.